Performance of the northern states: a comparative analysis - Joseph, Mathew (2004)
The northern states, which contribute about a half of the country's foodgrains production and over a four-fifths of milk, sugar cane and potato, have reached the limit of their agricultural growth for various reasons. This in turn has led to the falling growth of its industry and services sectors as well. Employment in agriculture has remained high at two-thirds of the labour force in the big states of Uttar Pradesh and Rajasthan. An attempt has been made in this paper to understand the various facets of underperformance of the northern states in comparison with other regions and to suggest the possible ways by which these states could improve their future economic and social performance. - Reproduced.
Keywords: Agricultural products